Physiological studies of a moderately halophilic bacterium, Vibrio costicola. - Choquet, Christian. (University of Ottawa (Canada), 1990)
In vitro protein synthesis in Vibrio costicola (polyuridilic acid (poly(U)) -directed incorporation of phenylalanine) was studied. As shown previously (Kamekura and Kushner, 1984), Cl$\sp-$ ions inhibited protein synthesis. The inhibitory effects were partly reversed by glutamate and betaine, both of which are concentrated within cells of V. costicola. Washing ribosomes with inhibitory NaCl concentrations did not interfere with their ability to carry out protein synthesis later in optimal (low) salt concentrations. The main site of action of Cl$\sp-$ in this system is on the binding of ribosomes to the messenger RNA. I studied the protein synthesizing machinery of V. costicola using cell-free protein synthesis systems directed by natural mRNAs. One system, the endogenous system, was directed by a mixture of unidentified messengers present in V. costicola, the mRNAs endogenous to these cells. In another system, I have shown that the viral mRNA, that of the coliphage R17, directs the incorporation of ($\sp $C) valine with cellular extracts of V. costicola. The ionic requirements of both systems were similar; both were most active at NH$\sb4\sp+$ (as ammonium glutamate) and Mg$\sp{++}$ concentrations of 250-300 mM and 8 mM, respectively. As was the case with the poly(U) system, Cl$\sp-$ also inhibited protein synthesis in these systems. Added sodium or potassium glutamate inhibited the R17 RNA system but stimulated the endogenous system. It is believed that Cl$\sp-$ is more deleterious to the initiation than to the elongation of protein synthesis, and that glutamate stimulates elongation. Betaine stimulated the activity of both systems, but did not show the same protective effects against Cl$\sp-$ as those observed in the poly(U) system. I have successfully isolated a crude preparation of initiation factors of V. costicola. These factors were released from the ribosomes at a NH$\sb4$Cl concentration much higher than that required for the isolation of the initiation factors of E. coli (1.0 M). Cl$\sp-$ was more inhibitory to the retention of ($\sp $C) fmet-tRNA on nitrocellulose filters, than to the retention of ($\sp3$H) R17 RNA; the retention of these substances was presumably due to the action of IF$\sb2$ and IF$\sb3$, respectively. The enzymes choline dehydrogenase and betaine aldehyde dehydrogenase, which are involved in the synthesis of betaine from choline, were identified in V. costicola. Both enzymes are probably inducibly formed in the presence of choline and seem to be osmoregulated. V. costicola accumulates betaine in response to increasing external NaCl; the intracellular betaine concentration in cells grown in media containing 1.0 and 3.0 M NaCl is 0.25 and 1.2 M, respectively. This accumulation of betaine is also affected by the external concentration of choline. At the lowest choline concentration (0.002%), there is no difference in betaine concentration between cells grown in media containing 0.5, 1.0 and 2.0 M NaCl, while cells grown in the presence of 3.0 M NaCl have only slightly more (0.4 M). These results suggest that betaine may not be the only compatible solute in V. costicola and/or that it may be synthesized through an alternative pathway, and that these cells may also employ other means to maintain turgor pressure. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.